Neutrophil–Lymphocyte and Platelet–Lymphocyte Ratios are Predictors of Lung Malignancy - Sutanto, Yusup S.; Rudiannor, Muhammad; Aphridasari, Jatu; Kurniawan, Hendra (Journal of Biomedicine and Translational Research, 2024)
Background: Inflammatory cells play an essential role in the neoplastic process by stimulating cancer proliferation, survival, and migration. Neutrophil-lymphocyte and platelet-lymphocyte levels can be used as the inflammatory tissue damage markers in cancer patients.Objective: This study aimed to analyze the increase of neutrophil-lymphocyte ratio (NLR) and platelet–lymphocyte ratio (PLR) as the predictive factors for lung malignancy.Methods: This study was a diagnostic cross-sectional study design in lung tumor patients at Dr. Moewardi Hospital Surakarta from August to October 2018. The subjects (60) were selected with consecutive sampling who take lung cancer diagnostic tests and divided into two groups of patients with lung tumors (30) and healthy (30) as control. The diagnostic procedures and neutrophil–lymphocyte and platelet–lymphocyte ratios calculation were performed on both groups. The optimum cutoff values for the NLR and PLR were calculated from the receiver operating curve analysis.Results: The statistical test found a significant difference in the neutrophil–lymphocyte and platelet–lymphocyte ratios between cancer patients and control (p = 0.0000). The lung cancer group exhibited an increase in the NLR with 90.0% sensitivity and 96.7% specificity with a cutoff of 2.71. The platelet–lymphocyte ratio had a cutoff of 136.63 at 83.3% sensitivity and 80.0% specificity.Conclusion: The increase of neutrophil-lymphocyte and the platelet-lymphocyte ratio can be used as a predictive predictor of lung malignancy.